Use of collard green stalks as environmental enrichment for cockatiels ( Nymphicus hollandicus ) kept in captivity - Carvalho,T.S.G. (2017)
ABSTRACT The objective of this study was to evaluate the influence of collard green stalks as environmental enrichment on the behavior of cockatiels (Nymphicus hollandicus) maintained in captivity. Sixteen birds were housed individually in cages and fed a commercial diet for parrots and seed mix, with water ad libitum during 12 days in climatic chamber with temperature and relative humidity simulating tropical conditions. The animals (n = 8) were divided into two groups, control and enriched, and the experimental period was divided into two phases (during and after enrichment) of four days each. The collard green stalks were used as enrichment only during the first period of the experiment, daily changed and maintained only during the day. The stalks increased the feed intake and decreased the sleep activities. No effect was observed on the body surface temperature, locomotion, maintenance and other resting activities. Small undesirable activities were detected. It was concluded that collard green stalks can be used as environmental enrichment, becoming part of food preferences of cockatiels. However, its use does not significantly alter the behavior of birds kept in captivity